On the continuum from mainstreaming to inclusion: the development of the approaches towards students with special needs and their expression in the educational frameworks in Israel - Bar, Nava; Kizel, Arie (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The State of Israel, like other developed countries around the world, engages intensively in the thinking about and care of students with special needs (SwSN). Israel attempts to open rang of possibilities to this population in its considerable diversity, while responding to the challenges faced by the population of students defined in Israel as „special education”. This article presents the developing approaches, which are at the basis of the special educational system in Israel, as a case study of the reference to SwSn. The first part of the article presents the ideological elements of the special education system in Israel throughout its historical development, and the second part presents the way in which the continuum of the educational frameworks was understood to serve the educational perception.